African Red Slip Ware and African Cooking Ware from the military camp of the legio II Parthica at Albano Laziale/Italy - Clara Formato, Lucia (Rei Cretariae Romanae Fautorum Acta, 2017)
The so called “Castra Albana”, legionary camp of the legio II Parthica, is situated in the region of Lazio, 25 km south-east of Rome, in the historical centre of the present-day Albano Laziale. The legionary camp, with a size of about 10,4 ha, is situated on a slope at an altitude of 390–430 m above sea level, 600m south of the lake of Albano and about 50m north of the ancient via Appia. Several ancient monuments, under these the remains of the military site, are preserved and still visible in the actual inner city of Albano Laziale. This was, beside the fact that the camp is the only roman legionary camp on Italian terrain, one of the reasons why it has been attracting the interest of various scholars since the beginning of the 16th century. A synopsis of the history of research was presented in 1975 by E. Tortorici in his comprehensive publication about the Castra Albana. In addition to the work of Tortorici, rescue excavations must be mentioned, that took place in the historical center of Albano Laziale during the last 40 years and were carried out by the Soprintendenza per i Beni Archeologici del Lazio. Further excavations were part of the DFG-supported project “Dalla villa imperiale ai Castra Albana – Von der Kaiservilla zu den Castra” of the German Archaeological Institute (DAI) of Rome. During this project it was possible to investigate parts of the interior surface of the legionary camp under the guidance of A. W. Busch and S. Aglietti in the years 2010, 2012 and 2014.